PELESTARIAN RONDANG BINTANG DI KABUPATEN SIMALUNGUN, SUMATERA UTARA - Nusantari, Indah; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Each region in Indonesia has its own characteristics and uniqueness, this can be seen from the traditions and culture that exist in that area. Likewise, Simalungun Regency has so many traditions that are still there today and are still being preserved, one of which is the Rondang Bintang tradition. The purpose of this research is to find out about Rondang Bintang, how the procedures for implementing Rondang Bintang, the values contained in the Rondang Bintang tradition, and the role of the government in preserving Rondang Bintang. The method used in this research is qualitative. The data obtained from the interviews were then analyzed in their own language. This research has been carried out since the beginning of the title of this research until this thesis is completed. The data collection techniques are Observation Technique, Interview Technique, Documentation Technique and Literature Technique. As for the results of this study, some of the people of Simalungun generally cultivate rice and corn as commodities, and have a habit after harvesting to hold a thanksgiving for the harvest obtained, the community calls it Rondang Bintang. Rondang Bintang is a tradition that is carried out after the harvest season as a thanksgiving for the success of the big harvest and it is during this opportunity that parents will give advice to young people about the types of life karma and deliberation for the improvement of tomorrow. However, at this time Rondang Bintang has been taken by the government and it is the government that regulates the timing of its implementation and so on the series of events. However, the government also has an important role in its preservation, one of which is providing a budget for this activity..Key Words: Preservation, Rondang Bintang